Pembekalan Public Speaking: Seni Berkomunikasi Secara Lisan Yang Efektif Bagi Tenaga Administrasi Sekretariat Dewan Kota Bandung - Purnamawati, Ami (LPPM Universitas Koperasi Indonesia, 2025)
The Secretariat of Council is the institution supporting certain services for Regional People's Representative Council. Some of the main functions are finance management and secretariat administration. In empowering its employees, the secretariat of council designed the three-day provisioning program. It was aimed to facilitate the employees of the council in conducting their duties. Some topics in widening their insights were the correlation between recess and regional development; report of regional finance management as well. During conducting their jobs, they certainly communicate with both internal public and external one, in this case they were also provided with the knowledge of effective communication specifically public speaking. The participants following this program were 45 employees whose working periods were various. The presenter delivered the public speaking topics using some methods such as games, presentation, quiz and discussion. The participants gave positive feed back during whole phases of the public presentation session.